PENTINGNYA EDUKASI DAN SKRINING PEMERIKSAAN TEKANAN DARAH DAN LINGKAR PERUT DI ATISA DIPAMKARA KARAWACI - Lontoh, Susy Olivia; Novendy; Irawaty, Enny; Dwi Putra, Muhammad Dzakwan; Razaan, Muhammad Naufal (Jurnal Serina Abdimas, 2024)
Uncontrolled high blood pressure and obesity are global health challenges. Based on the initial survey, participants felt there was no need to carry out regular pressure checks and did not know the importance of measuring abdominal circumference. The Tarumanagara University Faculty of Medicine community service team carried out educational activities on the importance of measuring blood pressure and abdominal circumference for early detection and prevention of hypertension and obesity. The target of the blood pressure and abdominal circumference measurement activity was teaching staff Atisa Dipamkara who was suspected of having high blood pressure and whose family history included hypertension and obesity. The method of implementing the activity is checking blood pressure and waist circumference and direct education regarding the results of blood pressure and abdominal circumference. Screening activities for blood pressure, abdominal circumference and education on the importance of monitoring blood pressure and abdominal circumference measurements were carried out on Monday, September 25 2023, at 7.30-13.00 at Atisa Dipamkara. The service activity was attended by 24 participants consisting of 7 (29.2%) male participants and 17 (70.8%) female participants. The age range of participants is 23-56 years. The mean systolic blood pressure was 114.79 mmHg and the maximum systolic blood pressure was 150 mmHg. The mean diastolic blood pressure was 79.92 mmHg and the maximum diastolic blood pressure was 90 mmHg. Based on the results of the examination, the participants' systolic and diastolic blood pressure were categorized as hypertension. The average abdominal circumference measurement result was 88.33 cm and the maximum abdominal circumference was 113 cm, so based on the results above it was found that the participant's abdominal circumference was categorized as obese.